Adapting The Mysteries of Udolpho’s Musicality into Real Music: An Impossible Task? - Lucie Ratail (Humanities)
The Mysteries of Udolpho was published at a time when poetry and music were being redefined, along with the notions of imitation and expression. From a precedence of word over music, theorists, musicians and composers started reconsidering the hierarchy of arts, which led to a new appreciation of both sung music and instrumental music. Ann Radcliffe’s novel is replete with pleasing sounds and mysterious melodies, working both as part of her décor and general soundscape and as a key element of the narrative. Given the novel’s musical profusion and versatility, one may wonder how to adapt its musicality into actual music. This paper, therefore, endeavors to define the balance of imitation and expression in The Mysteries of Udolpho and questions the ability of other media, especially those relying on sounds, to adapt its musical richness. It first focuses on the novel’s inscription in the larger context of musical theory, before delving into the limits of language’s sound mimesis and its counteracting expressivity. The final part is a case study of three artworks inspired by Radcliffe’s novel: John Bray’s song “Soft as yon’s silver ray that sleeps”, Catherine Czerkawska’s radio dramatization The Mysteries of Udolpho, and Marc Morvan and Benjamin Jarry’s album Udolpho.